(3JhVjM GdajI GHf eGdcs - (3GdMSf Hf bGSe Hf YHO Gddg GdeQGOj GdeUQj, HOQ GdOjf CHh eMeO, GHf Ge bGSe , J (B749 (3g` s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3CMeO Hf eMeO Hf YHO GdeYi Gdeci GdeGdci s)
(3ChdgG (B:s
(3bGd GdTjN GdeQGOi GdMeO ddg hGdTcQ dg hHYO agPG JhVjM GdebGUO GHf eGdc QMeI Gddg jMdh eYGfjgG Ydi WdGHgG hjXgQ eMGSfgG dNWGHgG s
(3BNQgG (B:s
(3TQhW GdChd Cf jchf eUOQkG hGdKGfi Cf jJMO hbJg hhbJ YGedg hgh GdeYdd Hg NJe GdcJGH HMeO Gddg JYGdi s
(3GdfSNI HgG MhGTs
(3HChdg GdYOjO ef GdJedcGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs